Case report: Endodontic treatment of a permanent maxillary first molar with three roots and six root canals : Opis primera: Endodontsko zdravljenje prvega zgornjega stalnega kočnika s tremi koreninami in šestimi koreninskimi kanali - Novak, Marko; Štamfelj, Iztok (Acta Medico-Biotechnica, 2023)
Purpose: This study aimed to report the diagnosis and management of a permanent maxillary first molar (PMFM) with unusually complex root canal morphology.Case report: A 30-year-old male patient was referred to the endodontic department to continue endodontic treatment of the left PMFM. The referring dentist could not establish the patency of the canals in the mesiobuccal and distobuccal roots. Radiographically, the tooth had three almost straight roots associated with periapical radiolucencies, indicating periapical periodontitis. The examination of the pulp chamber floor, using a dental operating microscope, revealed the presence of six root canal orifices, three in the mesiobuccal root, two in the distobuccal root, and one in the palatal root. No confluence of multiple canals was detected using the electronic apex locator and K-files. The canals were shaped and cleaned with reciprocating nickel-titanium instruments and obturated using gutta-percha cones and a bioceramic sealer. After 2 years, the patient was asymptomatic and the tooth was clinically and radiographically without pathological findings.Conclusions: Careful examination of the pulp chamber floor using magnification and illumination is important for successfully managing complex canal morphologies. During endodontic treatment, dentists must consider that the PMFM may have more than four root canals.